Multicomponent density functional theory: Including the density gradient in the electron-proton correlation functional for hydrogen and deuterium - Tao, Zhen; Yang, Yang; Hammes-Schiffer, Sharon (The Journal of chemical physics, 2019)
Multicomponent density functional theory (DFT) has many practical advantages for incorporating nuclear quantum effects into quantum chemistry calculations. Within the nuclear-electronic orbital (NEO) framework, specified nuclei, typically protons, are treated quantum mechanically on the same level as the electrons. Previously, electron-proton correlation functionals based on the local density approximation (LDA), denoted epc17 and epc18, were developed and shown to provide more accurate proton densities and energies compared to the neglect of electron-proton correlation, but a quantitatively accurate description of both densities and energies simultaneously has remained elusive. Herein, an electron-proton correlation functional that depends on the electron and proton density gradients, as well as the densities, is derived and implemented. Compared to the LDA functionals, the resulting generalized gradient approximation functional, denoted epc19, is able to simultaneously provide accurate proton densities and energies, as well as reproduce the impact of nuclear quantum effects on optimized geometries. In addition, without further parameterization, the NEO-DFT/epc19 method provides accurate densities and energies for deuterium as well as hydrogen. These results demonstrate that the form of the epc19 functional is able to capture the essential aspects of electron-proton correlation and highlights the importance of including gradient terms. This approach will enable the exploration of nuclear quantum effects and isotope effects in a wide range of systems.